Multiplex Matrix Metalloproteinases Analysis in the Cerebrospinal Fluid Reveals Potential Specific Patterns in Multiple Sclerosis Patients - Castellazzi, Massimiliano; Ligi, Daniela; Contaldi, Elena; Quartana, Davide; Fonderico, Mattia; Borgatti, Luca; Bellini, Tiziana; Trentini, Alessandro; Granieri, Enrico; Fainardi, Enrico; Mannello, Ferdinando; Pugliatti, Maura (Frontiers in Neurology, 2018)
Background. Matrix metalloproteinases (MMPs) are pleiotropic enzymes involved in extracellular protein degradation and turnover. MMPs are implicated in the pathogenesis of many neurological diseases, including multiple sclerosis (MS). Objective. To search the level of MMPs in the cerebrospinal fluid (CSF) of MS patients and detect possible disease-specific patterns. Methods. CSF samples from 32 MS patients and, from 22 control subjects with other neurological diseases (OND) were analysed. The Bio-Plex Pro Human MMP 9-Plex Panel (Bio-Rad) was used for the quantification of MMP-1, MMP-2, MMP-3, MMP-7, MMP-8, MMP-9, MMP-10, MMP-12, MMP-13. Results. CSF MMP-1, MMP-10 and MMP-12 levels were significantly reduced in MS as compared with OND. In MS patients’ CSF: (i) MMP-1 levels were significantly higher in women vs. men; (ii) MMP-10 concentrations were higher in patients with CSF-restricted IgG oligoclonal bands, and (iii) MMP-7 levels were increased in patients with longer disease duration. MMP-7 and MMP-12 levels significantly and directly correlated with age in the overall study population. Conclusions. Our study contributes to investigating the role of MMPs in MS, with regard to CSF immunological features and disease duration. Sex-specific differences were also detected in MMPs CSF levels.